Genomics and immunity of the Mediterranean mussel Mytilus galloprovincialis in a changing environment. Issue 90 (July 2019) - Figueras, Antonio; Moreira, Rebeca; Sendra, Marta; Novoa, Beatriz
Abstract: The Mediterranean mussel ( Mytilus galloprovincialis ) is a marine invasive species cultured all over the world. Mussels are an appreciated resource in local aquaculture enterprises because of their robust production and resilience that translates into a reliable economic value. So far, no massive mortalities have been reported in natural or cultured populations of this species. In the last years, the knowledge about its immune system has greatly improved but there are still many questions to be answered. One of them is why mussels, with their high filtering activity, are able to be exposed to a high number of potential pathogens without getting infected and without developing an elevated inflammatory response. The sequencing of the mussel genome has revealed a very complex organization with high heterozygosity, abundance of repetitive sequences and extreme intraspecific sequence diversity among individuals, mainly in immune related genes. Among those genes, antimicrobial peptides are the most expressed gene families in mussels, highly polymorphic and with antimicrobial effect against molluscs pathogens, but also against pathogens of lower vertebrates and humans. The combination of a complex genome with the adaptation of mussel immune system to a changing environment could explain this high variability, not only in immune-related genes, but also in the functional response among individuals sampled in the same location and date.